Global integration and technology transfer - Hoekman, Bernard M.; Javorcik, Beata K. Smarzynska (New York : Palgrave Macmillan ; Washington, DC : World Bank, 2006)
The trade research group at the World Bank has undertaken innovative empirical studies of the processes under which technology transfer occurs and its impacts on local economies. This volume brings together the fruits of this endeavour and offers various perspectives and information on this central issue for development.
Includes bibliographical references and index.
oif 21/08/15
Loan
Keywords: International economic integration; International trade; Investments, Foreign; Technology transfer; Industrial productivity